Karta Polaka – narzędzie politycznego wpływu czy tarcza w ręku Polonii? - Kakareko, Ksenia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The law on the Polish Charter is an element of a certain process, noticeable in Central and Eastern Europe, the purpose of which is to reinforce and retain contacts of respective states with immigrants, that is the members of the nation that predominates in each state who live abroad. The regulations which the Polish side has introduced in order to simplify border crossing for individuals of Polish origin by introducing special visas and the Polish Charter have stirred a profound political and social discussion in Belarus. Belarussian society does not have its own national identity, and is not sufficiently developed. The western part of Belarus is a multicultural region. This allows the dwellers of this region to declare themselves to be of practically any nationality as need arises. It may be concluded then that the Polish Charters, issued by Polish diplomatic posts, do not reflect the number of the actual members of the Polish minority. The applications for a Polish Charter are frequently triggered by economic aspects and the assessment that it pays to be a Pole.